AN ANALYSIS OF CODE SWITCHING USED IN PHOTO CAPTION BY FACEBOOK USER - Ovella Melvia; Yuliyanti Yuliyanti; Lilis Suryani (PROJECT (Professional Journal of English Education), 2019)
The aims of this research are to identify the types of the code switching appeared on Facebook for the reason phenomena and to investigate the reasons that affect the occurrence of code switching in Facebook. This research uses qualitative method with Hoffman (1991) and Saville-Troike (1986) theories. The data were collected from photos caption and status on Facebook during twenty days from 1st January 2018 to 20th January 2018, that were posted by 90 users who were followed by the researchers on Facebook. 120 data have found on status and photo caption facebok. The result of this research shows that there are three types of code switching on Facebook, namely Inter-sentential switching with 54 data, Intra-sentential switching with 50 data, and Emblematic switching with 16 data. Besides that there are five reasons which influence the use of code switching on Facebook, namely talking about particular topic with 39 cases found, quoting somebody else with 13 cases found, being emphatic about something (express solidarity) with 45 cases found, Interjection (inserting sentence fillers or sentence connectors) with 10 cases found, and real lexical need with 13 cases found. The dominant reasons which influence the use of code switching on Facebook are being emphatic about something (express solidarity) with 45 cases.